BUSINESS STRATEGY ANALYSIS OF PT SOHO REGULAR PHARMACEUTICAL INDUSTRY - Anna Karina Algustie; Basu Swastha Dharmmestha (Faculty of Pharmacy, Universitas Gadjah Mada)
A competitive company is a company which has and implements business strategies that can act in response to external conditions and improve their internal capabilities. The objectives of this study were to identify and evaluate whether the company business strategy is suitable with its external and internal conditions and to arrange alternative strategies based on external and internal conditions. The research was a descriptive analysis. The data were collected through deep interviews and internal observation to the company, also supporting data from secondary source. The data were analyzed by: External and internal analysis with External Factors Evaluation Matrix (EFE) and Internal Factors Evaluation Matrix (IFE); Alternative strategies formulation was done through Strength-Weakness-Opportunity-Threat Matrix (SWOT), Internal-External Matrix (IE), Boston Consulting Group Matrix (BCG), and Grand Strategy Matrix; Decision stage was done by Quantitative Strategic Planning Matrix (QSPM). The results showed that there was a change on competitive conditions so that company needed to modify the strategy implemented. EFE matrix result was 3.02 which showed that the company’s strategies were responsive to the external conditions, while IFE matrix result was 2.78 which showed that company had quite strong internal capabilities. Alternative strategies formulation through SWOT, IE, BCG and Grand Strategy matrix analysis and the decision through QSPM analysis result showed that “Improving product variation with new product development or cooperation with other companies” was the most suitable with QSPM score 6.183 followed by “Market development and market penetration through existing products with QSPM score 5.726.Keywords: Business Strategy Analysis, PT Soho Industri Pharmasi, SWOT, QSPM